Engaging fathers(to-be): a pilot study on the adaptation and programme experience of SMS4baba intervention in Kenya’s informal settlements - Vibian Angwenyi; Richard Fletcher; Paul Murimi Mwangi; Margaret Kabue; Rachel Odhiambo; Stephen Mulupi; Emmanuel Kepha Obulemire; Eunice Njoroge; Eunice Ombech; Mercy Moraa Mokaya; Moses Wesala; Joyce Marangu; et al. (BMC Public Health)
Abstract Background Engaging fathers(to-be) can improve maternal, newborn, and child health outcomes. However, father-focused interventions in low-resource settings are under-researched. As part of an integrated early childhood development pilot cluster randomised trial in Nairobi’s informal settlements, this study aimed to test the feasibility of a text-only intervention for fathers (SMS4baba) adapted from one developed in Australia (SMS4dads). Methods A multi-phased mixed-methods study, which included an exploratory qualitative phase and pre-post evaluation of the adapted SMS4baba text-only intervention was conducted between 2019 and 2022. Three focus-group discussions (FGDs) with 19 fathers were conducted at inception to inform SMS4baba content development; two post-pilot FGDs with 12 fathers explored the acceptability and feasibility of SMS4baba implementation; and 4 post-intervention FGDs with 22 fathers evaluated SMS4baba programme experiences. In the intervention phase, 72 fathers were recruited to receive SMS4baba messages thrice weekly from late pregnancy until over six months postpartum. A pre-enrolment questionnaire captured fathers’ socio-demographic characteristics. Pre-post surveys were administered telephonically, and outcome measures evaluated using a paternal antenatal attachment scale, generalised anxiety disorder scale (GAD-7), patient health questionnaire (PHQ-9), and researcher-developed questionnaire items assessing paternal involvement, childcare and parenting practices. Qualitative data were analysed using a thematic approach. Statistical analysis performed included descriptive statistics, tests of association, and mixed model regression to evaluate outcomes. Results Fathers perceived SMS4baba messages as educational, instilling new knowledge and reinforcing positive parenting, and helped fathers cope with fatherhood transition. High levels of engagement by reading and sharing the texts was reported, and fathers expressed strong approval of the SMS4baba messages. SMS4baba’s acceptability was attributed to modest message frequency and utilising familiar language. Fathers reported examples of behaviour change in their parenting and spousal support, which challenged gendered parenting norms. Pre-post measures showed increased father involvement in childcare (Cohen’s d = 2.17, 95%CI [1.7, 2.62]), infant/child attachment (Cohen’s d = 0.33, 95%CI [-0.03, 0.69]), and partner support (Cohen’s d = 0.5, 95%CI [0.13, 0.87]). Conclusion Our findings provide support for father-specific interventions utilising digital technologies to reach and engage fathers from low-resource settings such as urban informal settlements. Exploration of text messaging channels targeting fathers, to address family wellbeing in the perinatal period is warranted. Trial registration This study was part of the integrated early childhood development pilot cluster randomised trial, registered in the Pan African Clinical Trial Registry on 26/03/2021, registration number PACTR202103514565914.